Growth curves of broilers fed different nutritional relationships using the Gompertz model - Luís Filipe Villas Bôas de Freitas; Antonio Gilberto Bertechini; Alisson Hélio Sampaio Clemente; Felipe Augusto Fernandes; Diego Alexsander Bauth; Tales Jesus Fernandes (Acta Scientiarum. Animal Sciences, 2022)
The study aimed to evaluate performance and growth curves of broilers fed different nutritional relations. A total of 1,440 Cobb-500 male day-old chicks were assigned to eight treatments in a 2 x 2 x 2 factorial arrangement with six replicates of 30 birds each. The main factors were nutritional density (control and high), lysine source (HCl and sulfate), and calcium pidolate (presence and absence). Analyses were made for body weight gain (BWG), and feed conversion rate (FCR) at 21, and 42 days of age. The growth curves were adjusted by weighing a bird per plot every three days. Data for BWG were tested by ANOVA to evaluate the effects of treatments and their interactions at 5% significance, and the Gompertz model was adjusted by NLS. Birds fed a high nutritional density had higher BWG and lower FCR. Calcium pidolate and different sources of lysine did not influence the FCR of broilers, however a triple interaction was evidenced for BWG at 1 to 42 days of age. The day with maximum gain adjusted by Gompertz of all treatments was at the 32nd day of age and the maximum weight (A) was around 5.85 kg.